2020
DOI: 10.32098/mltj.03.2020.03
|View full text |Cite
|
Sign up to set email alerts
|

Kinesio Tape In Shoulder Rotator Cuff Tendinopathy: A Randomized, Blind Clinical Trial

Abstract: Background. Shoulder pain is a very common musculoskeletal disorder that affects many people, with rotator cuff (RC) injury as one of its main causes. Objective. To analyze the efficacy of KT, both isolated and associated with exercise, on pain and function of patients with shoulder RC injuries. Method. A randomized, blind clinical trial with sixty (60) participants with RC injuries, randomized into exercise group (EG), in which participants performed an exercise protocol; kinesio tape group (KTG), with applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…They formulated three groups in their study: first group was of EG, second was the KT group and third was the exercise KT group (EKTG). They found that all groups depicted an improvement in pain and functional parameter but EKTG had demonstrated much better results as compared to other two groups (Martins da Silva et al, 2020). Our study is also coherent with these results.…”
Section: Discussionsupporting
confidence: 90%
“…They formulated three groups in their study: first group was of EG, second was the KT group and third was the exercise KT group (EKTG). They found that all groups depicted an improvement in pain and functional parameter but EKTG had demonstrated much better results as compared to other two groups (Martins da Silva et al, 2020). Our study is also coherent with these results.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of included studies were from Europe (21.40.38%) and the remaining from Asia, (18, 34.6%), South America (5 (9.62%), North America (4,7.69%), and Australia (4 (7.69%). 22 out 52 studies had published protocols available [ 32 , 33 , 36 , 37 , 40 , 43 , 44 , 47 , 53 , 58 , 61 , 65 , 68 , 69 , 71 , 72 , 74 76 , 78 , 80 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall risk of bias assessment ( S4 Appendix ) for pain found 19 studies at high risk [ 34 , 38 , 39 , 41 , 43 , 45 48 , 57 59 , 64 , 66 , 70 , 78 , 79 , 81 , 84 ], 21 with some concerns [ 33 , 35 , 37 , 40 , 42 , 44 , 51 , 52 , 54 , 56 , 60 62 , 65 , 68 , 77 , 80 , 82 , 85 ] and 4 at low risk [ 53 , 71 , 73 , 74 ]. For ABD ROM, 9 studies had high risk [ 34 , 41 , 57 , 59 , 62 , 70 , 75 , 81 , 84 ] and 6 had some concerns [ 35 , 40 , 49 , 56 , 77 ,…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that the high fitness level of the healthy athletes and their regular training would reduce the possibility of the additional effect of kinesio taping. In 39 patients with partial rotator cuff tendinopathy, 4 weeks of kinesio tape applied over 3 regions (the supraspinatus and infraspinatus, deltoid muscle belly and an I-shaped tape anchoring the others from the coracoid process towards the scapular spine) found that kinesio taping increased muscle strength of flexors and internal rotators while kinesio taping and exercise increased muscle strength in all directions (50). In our study, kinesio taping was applied only to healthy people and in direction of facilitation, whereas Martins de Silva et al applied it with the muscle inhibition method.…”
Section: Discussionmentioning
confidence: 99%